Effects of Chronic Hypoxic Environment on Cognitive Function and Neuroimaging Measures in a High-Altitude Population - Zhang, Ya Qing; Zhang, Wen juan; Liu, Jin hao; Ji, Wei zhong (Frontiers in Aging Neuroscience, 2022)
Objective: This study aimed to investigate the effects of long-term hypoxic environment exposure on cognitive ability and neuroimaging characteristics in a highland population in China. Methods: Health system workers in Maduo County (4300 m above sea level) and Minhe County (1700 m above sea level) were selected as research participants and divided into a high-altitude group and low-altitude group, respectively. Cognitive ability was assessed using the Montreal Cognitive Assessment (MoCA), Verbal Fluency Test (VFT), Symbol Digit Modalities Test (SDMT), Trail Making Test A and B, Digit Span Test (DST), and Rey Auditory Verbal Learning Test (RAVLT). All participants underwent a magnetic resonance imaging (MRI) scan, resting state functional MRI scan, and diffusion tensor imaging (DTI) to clarify changes in regional gray matter (GM) volume, anisotropy index (FA), local consistency (ReHo), and low-frequency oscillation amplitude (ALFF). Results: The high-altitude group had significantly lower MoCA, DST, VFT, RAVLT, and Trail Making Test A and B scores compared to the control group. No significant differences were found in SDMT score. Furthermore, compared to the low-altitude group, the high-altitude group had significantly lower GM density of the left olfactory cortex, right medial orbital superior frontal gyrus, bilateral insula, left globus pallidus, and temporal lobe (left superior temporal gyrus temporal pole, bilateral middle temporal gyrus temporal pole, and right middle temporal gyrus). In terms of FA, compared with the low-altitude group, the high-altitude group had lower values for the corpus callosum, corpus callosum knee, bilateral radiative corona, and left internal capsule. The high-altitude group had lower ALFF values of the left cerebellum, left putamen, left orbital inferior frontal gyrus, and left precuneus, but higher ALFF values of the left fusiform gyrus, bilateral inferior temporal gyrus, left orbital superior frontal gyrus and medial superior frontal gyrus, compared to the low-altitude group. There were no significant group difference in ReHo values. Conclusion: Our findings suggest that a chronic hypoxic environment can induce extensive cognitive impairment. Decreased GM density in multiple brain regions, damaged nerve fibers, and unbalanced neuronal activity intensity in different brain regions may be the structural and functional basis of cognitive impairment due to hypoxia.